Misinformation Drives Low Human Papillomavirus Vaccination Coverage in South African Girls Attending Private Schools - Milondzo, Tracy; Meyer, Johanna C.; Dochez, Carine; Burnett, Rosemary J. (Frontiers in Public Health, 2021)
Background: Cervical cancer, caused by persistent human papillomavirus (HPV) infection, is the leading cause of female cancer deaths in South Africa. In 2014, the South African National Department of Health introduced a free public sector school-based HPV vaccination programme, targeting grade 4 girls aged ≥9 years. However, private sector school girls receive HPV vaccination through their healthcare providers at cost. This study investigated HPV vaccination knowledge, attitudes and practices of caregivers of girls aged ≥9 years in grades 4-7 attending South African private schools. Methods: A link to an online survey was circulated to caregivers via an email sent to school principals of all private schools in four provinces enrolling girls in grades 4-7. Following a poor post-reminder response, a paid Facebook survey-linked advert targeting South African Facebook users aged ≥25 years nationally was run for 4 days, and placed on the South African Vaccination and Immunisation Centre’s Facebook page for 20 days. Results: Of 615 respondents, 413 provided HPV vaccination data and 455 completed the knowledge and attitudes tests. Most (76.5%) caregivers had good knowledge and 45.3% had positive attitudes. Of their daughters, 19.4% had received ≥1 dose of HPV vaccine. Of caregivers of unvaccinated girls, 44.3% and 41.1% respectively were willing to vaccinate their daughters if vaccination was offered free and at their school. Caregivers of unvaccinated girls were more likely (odds ratio [OR]: 3.8) to have been influenced by ‘other’ influences (mainly online articles and anecdotal vaccine injury reports). Of caregivers influenced by their healthcare providers, caregivers of unvaccinated girls were more likely (OR: 0.2) to be influenced by alternative medical practitioners. Caregivers of vaccinated girls were more likely to have good knowledge (OR: 3.6) and positive attitudes (OR: 5.2). Having good knowledge strongly predicted (OR: 2.8) positive attitudes. Having negative attitudes strongly predicted (OR: 0.2) girls being unvaccinated. Conclusion: Providing free school-based HPV vaccination in the private sector may not increase HPV vaccination coverage to an optimal level. Since misinformation was the main driver of negative attitudes resulting in less than 20% of girls being vaccinated, an advocacy campaign targeting all stakeholders is urgently needed.